An exploratory study on sosial innovation process among sosial enterprise in Malaysia [electronic resource] - Nor Aisah Hatta, 1994-, author 634573 (2017)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2017